Mental health and well-being in children - Nunes, Cristina (2022)
Mental disorders are the largest cause of the burden of disease in the world [1]. Evidence is accumulating on the broad impact of the well-being experienced during childhood and adolescence on physical and mental health across the course of a lifetime. In fact, most of the disease burden affecting adults has its onset during childhood and adolescence.